Influence of different cellulose/hemicellulose/lignin ratios on the thermal degradation behavior: prediction and optimization - Ornaghi, Heitor Luiz; Monticeli, Francisco M. [UNESP]; Neves, Roberta Motta; Agnol, Lucas Dall; Bianchi, Otavio (Springer Nature, 2021)
Vegetal fibers can be applied in several areas, from the medical field to the development of new advanced materials. They have a complex chemical structure including cellulose, hemicellulose, and lignin. Each component plays a different role in the thermal degradation. Apart from it, this study aims to simulate and predict different ratios of cellulose/hemicellulose/lignin in the thermal degradation behavior of a vegetal fiber. This study was divided into two distinct parts: (i) firstly, the thermogravimetric curves (TG) were simulated based on their chemical composition to verify the influence of each component ratio in the degradation behavior. Briefly, 100% hemicellulose sample showed the lowest Tonset, 100% lignin sample showed the highest residue, and 100% cellulose sample showed the lowest residue at 600 °C among all samples studied. (ii) Secondly, a prediction of the thermal behavior for any combination of cellulose, hemicellulose, and lignin was performed by using an artificial neural network (ANN) combined with a surface response methodology (SRM). The prediction curves presented high reliability with the experimental fit, which allowed the thermal degradation behavior prediction of a vegetal fiber with any cellulose, hemicellulose, and lignin ratio. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Artificial neural network; Cellulose/hemicellulose/lignin; Surface response methodology; Thermal behavior; Thermal degradation